2017
DOI: 10.1186/s13075-017-1239-7
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture decreased the risk of coronary heart disease in patients with fibromyalgia in Taiwan: a nationwide matched cohort study

Abstract: BackgroundThe aim of this study was to understand whether acupuncture can decrease the risk of coronary heart disease (CHD) in patients with fibromyalgia.MethodsUsing data from the Taiwanese National Health Insurance Research Database, we performed a propensity score-matched cohort study to analyze patients with fibromyalgia diagnosed between 1 January 2000 and 31 December 2010. Patients who received acupuncture treatment, beginning with their initial date of fibromyalgia diagnosis and extending to 31 December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…A modern medical study indicated that acupuncture can significantly increase blood flow in the skin and muscles of patients with FM,35 which is very important for reducing pain symptoms. As a primary mechanism of FM, the central sensitization of nervous system can decrease the pressure pain threshold, elicit hyperalgesia, and as a result, a noxious stimulus can cause more severe pain than in normal individuals 36,37. One recent animal study found that the upregulation of transient receptor potential vanilloid 1 and the phosphoactivation of extracellular signal regulated kinase were associated with mechanical hyperalgesia in FM model mice.…”
Section: Discussionmentioning
confidence: 99%
“…A modern medical study indicated that acupuncture can significantly increase blood flow in the skin and muscles of patients with FM,35 which is very important for reducing pain symptoms. As a primary mechanism of FM, the central sensitization of nervous system can decrease the pressure pain threshold, elicit hyperalgesia, and as a result, a noxious stimulus can cause more severe pain than in normal individuals 36,37. One recent animal study found that the upregulation of transient receptor potential vanilloid 1 and the phosphoactivation of extracellular signal regulated kinase were associated with mechanical hyperalgesia in FM model mice.…”
Section: Discussionmentioning
confidence: 99%
“…All public insurance systems were integrated into the National Health Insurance (NHI) program in Taiwan in 1995 as a single-pay program to serve all residents, with 99% of 23.74 million residents covered in 2009. It has offered insurance cover for Traditional Chinese Medicine (TCM, including; Chinese herbal medicines, acupuncture, and traumatology manipulative therapies) and conventional Western medicine (17,18). Intact registration files and original claim data of acupuncture utilization were collected in the Taiwanese National Health Insurance Research Database (NHIRD).…”
Section: Introductionmentioning
confidence: 99%
“…The NHI program covers not only Western medical services but also ambulatory care in TCM. All claims data from the NHI program are collected in the National Health Insurance Research Database (NHIRD), and researchers can use these datasets to evaluate the utilization of TCM for various diseases such as allergies [ 14 , 15 ], musculoskeletal diseases [ 16 18 ], metabolic disorders [ 19 , 20 ], gynecologic diseases [ 21 ], pediatric diseases [ 2 ], geriatric disorders [ 22 ] and cancer [ 23 , 24 ]. De-identified demographic characteristics (e.g., sex, date of birth, occupation and place of residence) and clinical information (e.g., diagnosis, management and treatment) are also provided in the database.…”
Section: Introductionmentioning
confidence: 99%